Social Responsibility and Ethics Issues in Today’s World: A Review - S. Vennila Fathima Rani; S. Jayakani (AG Volumes, 2023)
The field of study known as "Ethics and Social Responsibility" is expanding and diversifying. Ethical behavior necessitates the ability to behave freely; it cuts across all aspects of our lives; it is universal; it is inherent; and it reflects an absolute ideal. All the more reason to educate our society’s managers so they can steer clear of morally questionable actions like those exposed in today’s many business crises. The modern literature on ethics is unprepared to meet the demands of managers, who are primarily responsible for upholding ethical standards in the workplace. The formerly unquestioned values are now being seriously debated. There is a lack of unambiguous moral and ethical norms that can guide managers through thorny moral and ethical conundrums. Due to the fast-changing nature of the business world in the wake of the emergence of affluent societies and LPG ("Liberalization, Privatization, and Globalization"), this article focuses on the fundamentals of business ethics & social responsibility and how they can be put into practice at the organizational level.